Are Patients With Type 2 Diabetes Not Aware or Are They Unable to Practice Self-Care? A Qualitative Study in Rural South India - M. Anitha Rani; Vanishree Shriraam (SAGE Publishing, 2019)
Background: Lack of awareness and poor adherence to dietary, lifestyle modifications, and medications among patients with diabetes result in poor health outcomes. Aim: This study aimed to understand patients' perceptions about barriers to self-management of diabetes. Materials and Methods: This was a descriptive qualitative study among patients with diabetes attending a rural health center. Five focus group discussions were conducted with 8 to 11 participants using a topic guide. Results: Many were unaware of target levels and complications of diabetes. Some aspects of the dietary information were found to be quite confusing. Physical constraints prevented many from going for outdoor walking. They have not received any information on foot care. Conclusions: Understanding the barriers for self-care will help health care workers manage diabetes better.